Analysis of Teacher Readiness in Implementing the Independent Learning Curriculum - Cherly Afriani; Gimin Gimin; Hendripides Hendripides (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to determine (1) the readiness of teachers in implementing the independent learning curriculum. (2) the obstacles faced by teachers in implementing the independent learning curriculum. The background of this research is 21st century learning which requires teachers to be able to apply students' creativity, critical thinking, cooperation, problem solving, communication skills, social skills and character skills. However, teachers are not ready to apply the independent curriculum. The method used in this research is a quantitative descriptive method. The data source for this study was primary data obtained from questionnaires to all teachers at SMPIT Al-Andalus Pekanbaru and SMP Negeri 8 Pekanbaru with a total of 64 teachers. Data collection techniques used are documentation and questionnaires. The results showed that overall teacher readiness at SMPIT Al-Andalus Pekanbaru and SMP Negeri 8 Pekanbaru were quite ready to implement the Merdeka curriculum. In using learning facilities and infrastructure, teachers need to learn new things.